Cervical cerclage, pessary, or vaginal progesterone in high-risk pregnant women with short cervix: a randomized feasibility study. (2nd January 2021) - Care, A.; Jackson, R.; O'Brien, E.; Leigh, S.; Cornforth, C.; Haycox, A.; Whitworth, M.; Lavender, T.; Alfirevic, Z.
Abstract: Objective: To assess feasibility for a definitive randomized controlled trial (RCT) comparing three treatments for short cervix in a population at high risk for spontaneous preterm birth (sPTB) over a 1-year period. Design: Three arm, open label feasibility randomized clinical study. Methods: Women with singleton pregnancy with risk factors for sPTB (history of sPTB or prelabor premature rupture of membranes (PPROM) <34 weeks or significant cervical surgery), and short cervix on transvaginal ultrasound scan detected between 16 +0 and 24 +6 weeks gestation were randomized to receive either cervical cerclage, vaginal pessary, or vaginal progesterone 200 mg nocte. Pregnancy outcomes and treatment costs were collected from hospital records, NHS Reference costs, and British National Formulary costs. Main outcome measures: Feasibility targets were defined as (i) at least 55% of eligible women randomized; (ii) maximum 5% failure to adhere to the protocol per arm; (iii) maximum 5% loss to short-term follow-up. Results: Of 417 women screened between October 2015 and 2016, 25 (6%) were eligible for trial inclusion, of whom 18 (72%) agreed to participate at the rate 0.75 participants/site/month. Adherence to protocol was 100% in pessary and cerclage arms and 80% in vaginal progesterone arm (95% CI 24–100%). No participants were lost to follow up. Cost of interventions accounted for 6% (95% CI 2–10%) of overall health care expenditure. Conclusions: A definitive clinical trial comparing treatments for prevention of sPTB in high-risk women with short cervix is feasible but will be challenging due to small numbers of eligible participants.